ШАХС ИЖТИМОИЙ-ПСИХОЛОГИК ХУСУСИЯТЛАРИ ВА ИЧКИ ИМКОНИЯТЛАРИНИНГ МЕҲНАТ ФАОЛИЯТИДАГИ ЎРНИ - Елмуратова, А.У. (SCIENCE and SOCIETY, 2018)
The article deals with the attitude of the individual to work for the whole period of his entire work activity. There have been studied the issues of awakening the ability in the owner of the profession of love to his profession, the ability to give social-psychological attitudes about the created conditions to workers, about the direct impact of natural conditions.
Keywords: personality; profession; work; professional skill; leadership; age periods; culture of communication; ability; professional activity; mental activity